Rancang Bangun E-Commerce Pada Toko Bravo Sports - Zamli, Fitrah Faisal; Minartiningtyas, Brigida Arie (INFOTEKS (Information Technology, Computer and Sciences), 2020)
Bravo Sports Store is one of the shops or businesses engaged in the trade of sports equipment. In the process of selling goods, today the store is still using a conventional system that consumers must come directly to the store to buy the desired goods. Stores have been using technological advances to help disseminate information about goods sold by using social media such as BBM, Instagram, Facebook, and twitter. However, it is considered inefficient because of the large number of consumers. Social media is also not able to distinguish notifications between consumers who want to ask about goods and consumers who want to buy goods. In addition, the owner must also make continuous renewal of information items such as examples of quantities of goods and prices of goods which are then published back to the public. To overcome this the authors will design and build an e-commerce web. The result of e-commerce is a system can be used to process goods data, employee data, transaction data, order data, employee data, consumer data, and reports. Based on blackbox testing done can be concluded that has been successfully built a web e-commerce.